2016
DOI: 10.1155/2016/1849134
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effect of Head Injury by Helmet Type in Motorcycle Crashes: A Rural Korean Single-Center Observational Study

Abstract: Introduction. The goal of this study was to determine the preventive effect on head injury by helmet type: full face helmet (FFH), open face helmet (OFH), and half-coverage helmet (HCH). Methods. This is a retrospective observational study of motorcycle crash victims between June 2012 and May 2015 in a rural town in Korea. We performed multiple linear regression to predict the effect of each type of helmet compared to unhelmeted status in preventing head injury using dependent variables based on the Abbreviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
0
27
1
2
Order By: Relevance
“…[26] National Highway Traffic Safety Administration (NHTSA) has emphasized the importance of proper helmet usage according to international helmet laws based on analysis of fatal motorcycle crashes in USA, [27] and the fact of the proper helmet usage and the reduction of head injury and its severity is well established in the literature. [26,28] However, there is no significant difference between the presence of external head injury in helmeted and non-helmeted groups in our study, but 83% of internal head injuries were seen with non-helmeted riders. The fact of the use of helmet by the riders of this study has been determined by the Police investigation records as well as some characteristic injuries to the chin due to the buckle of the helmet strap.…”
Section: Discussioncontrasting
confidence: 67%
“…[26] National Highway Traffic Safety Administration (NHTSA) has emphasized the importance of proper helmet usage according to international helmet laws based on analysis of fatal motorcycle crashes in USA, [27] and the fact of the proper helmet usage and the reduction of head injury and its severity is well established in the literature. [26,28] However, there is no significant difference between the presence of external head injury in helmeted and non-helmeted groups in our study, but 83% of internal head injuries were seen with non-helmeted riders. The fact of the use of helmet by the riders of this study has been determined by the Police investigation records as well as some characteristic injuries to the chin due to the buckle of the helmet strap.…”
Section: Discussioncontrasting
confidence: 67%
“…Studies conducted in Western countries and Taiwan [17,[20][21][22][23][24][25] have reported that full-coverage helmets protect from head injuries. In line with previous results, our results indicated that standard helmets have a highly protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attempted to examine the effects of different helmet types on head and neck injuries. For example, studies [17][18][19][20][21][22] have reported that riders wearing open-face or half helmets had an increased risk of sustaining facial and neck injuries compared with riders wearing full-face helmets. Rice et al [23] concluded that novelty helmet or nonstandard helmet use was associated with an increased risk of fatal injuries compared with full-face helmet use after adjustment for speed and other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Sung et al (2016) reported that full-face and open-face helmets reduced the occurrence and severity of head injuries in Korea, whereas half-helmets did not.…”
Section: Discussionmentioning
confidence: 99%